KEPENTINGAN INDONESIA MEMUTUSKAN HUBUNGAN KERJASAMA DENGAN JP MORGAN CHASE BANK - Yunita, Octha Nur; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This thesis discusses the interests of Indonesia sever the relationship of cooperation with jp morgan chase bank. Indonesia terminated the cooperative relationship with jp morgan chase bank because jp morgan made a detrimental research for Indonesia. The jp morgan's research made Indonesia's downgrade rating from overweight to underweight. Indonesia did not accept the results of jp morgan research, because the research was not in accordance with the Indonesia situation at the time and jp morgan could not explain why it coul Indonesia’s downgrade from overweight to underweight, So Indonesia broke off cooperation with jp morgan on 1st january 2017 .The termination of this cooperative relationship uses the theory of foreign policy because the foreign policy Theory considers that policies used by other countries will help the country to achieve national interest. The national interest is aimed at maintaining the security of the political economy of Indonesia. This foreign policy theory breaks the relationship between Indonesia and jp morgan chase bank which is the reason of harm Indonesia and this disconnection is directed to the national interest.Indonesia terminated the relationship with jp morgan chase bank due to the inaccurate research of jp morgan and the disadvantage of Indonesia. the research entitled "Trump forces tactical changes" made by jp morgan on 13 November 2016. In the end Indonesia gave the letter of termination cooperation to jp morgan chase bank.From research jp morgan, the funds out of Indonesia amounted to 16 trillion. This happened for one week after jp morgan made a research rating of Indonesia.Keywords: jp morgan chase bank, interests, relationships